Evaluación de la fricción en arcos ortodóncicos de acero inoxidable con y sin recubrimiento vítreo aplicado por el método sol-gel (2009)
ABSTRACT: The aim of this in vitro study was to compare the static and dynamic frictional force generated between surfaces of metallic brackets and glass coated applied by the Sol-Gel method, and non coated wires. Methods: metallic brackets (0,018 x 0,025″), stainless steel wires (0,016 x 0,016″) and elastic ligatures were used in all frictional tests. All components were characterized using SE M and optical microscopy. The frictional force was evaluated using a machine of tests Testresources® in dry environment. Results: the results showed that the stainless steel wires without modification (control group) showed the lowest values of static friction force followed by the stainless steel wires group coated by Sol-Gel method and the wires group with thermic treatment (thermic group). For dynamic friction force, the Sol-Gel group showed the smallest values, followed by the control group and the thermal group. Conclusion: the evaluated coating did not show a better frictional performance applied on stainless steel brackets in comparison with the control group.